THE APPLICATION OF 21ST CENTURY LEARNING ASSESSMENT BY ENGLISH TEACHERS AT SENIOR HIGH SCHOOL - Ayni Ryanti; Hadriana Hadriana; Mahdum Adnan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
The 21st century is a century that is full of challenges. Advances in technology that are increasingly developing make humans have to be ready to accept various kinds of changes. Various competencies needed by students in the current era of globalization are often referred to as 21st-century skills, and the concept of education is known as 21st-century learning. Based on the times, the current assessment refers to 21st-century learning, which is related to critical thinking, creative thinking, communication skills, and collaboration skills. The application of 21st-century learning cannot be separated from 21st-century assessment. The purpose of the study in this paper is to determine whether the teachers were familiar with and applied 21st-century learning assessment or not, especially in learning English. This research used a descriptive qualitative research method by collecting data through observation, interviews, and documentation. The results of the study indicate that of the four 21st-century learning indicators, English teachers have started implementing 21st-century learning assessments. It can be concluded that English teachers have begun to adjust their assessment rubrics according to the indicators that exist in each type of skill possessed by students, namely critical thinking, creativity, collaboration, and communication skills.